La ricerca elettorale dell'Istituto Cattaneo. Continuità e cambiamento, interrogativi e metodi - Piergiorgio Corbetta; Arturo M.L. Parisi (QOE-IJES, 2018)
The present article relates the story of the electoral research project by Istituto Cattaneo since the early '60s up to 2001. It is a conceptual and methodological reenactment distinguishing three periods. A first phase (1958-1974) of quite exclusive attention payed to the continuity of both the political party system and the political behavior. A second phase (1975-1987) in which, under the pressure of electoral results strongly different from the past (i.e. referendum on divorce in 1974, regional election in 1075 and national election in 1976), studies were focused on cues of "change inside the continuity". Finally, in the third phase (1988-2001) the change - both on a structural and individual level - was the focus of scholars' attention. This transformation of the interpretative paradigms is view in relation to the research methods employed. Such methods progressively shifted from the ecological analysis of the vote based on official data of territorial aggregates to the analysis of self-reported individual behavior through surveys.